Exploring the train and airplane as transportation mode preferences among commuting students - Indah Susilowati; Arisanti Ayu Wardhani; Cici Musliha; Yohanes Dwi Mahardika; Yoseph Dennis Ardianto (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2024)
Transportation has significant role in urban life. Commuting students in universities in Semarang have several options in transportation modes. This study aimed to examine student preferences for train and airplane transportation modes and factors influencing it. Data of 110 students at several Semarang City Universities compiled by purposive sampling were then analyzed using descriptive statistics method. The results showed that most students prefer train transportation modes rather than airplanes. Regarding the level and quality of service, trains provide better services at cheaper, faster, and more practical prices. Meanwhile, based on the quality of service, aircraft transport offers better safety and comfort than Train transport. Although there are differences in the level and quality of comfort, students preferred to use train since the differences are not significant.